Análise comparativa entre custos reais x orçados dos insumos significativos de uma residência unifamiliar, na cidade de Ipanguaçu/RN - Dantas, Max Jorrany de França (Universidade Federal Rural do Semi-Árido, 2020)
This work approaches a comparison between the real and budgeted costs, of the significant inputs, generated by an ABC curve, of the construction of a single-family residence, in the municipality of Ipanguaçu / RN. With regard to the coefficients of these inputs, the budget was generated based on the SINAPI Table, reference month October 2020, and the quotation of material prices was carried out in construction stores in the municipality. The study considered the typology R1-B, which, according to the standard ABNT NBR 12721: 2006, is characterized as a standard project, low standard single-family residence - 1 floor, with 2 bedrooms, living room, bathroom, kitchen and tank environment, with an area total of 58.64 square meters. From the budget, an ABC curve was generated, with significant inputs, to compare its values in the local market. The results obtained reveal the importance of good planning and work execution schedule, so that there are no significant differences in relation to the costs expected in the construction progress.
Monografia
Keywords: Análise comparativa; Construção civil; Orçamento; Custo Orçado; Custo real; Comparative analysis; Construction; Budget; Budgeted cost; Real cost; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA